Violent and non-violent crime against adults with severe mental illness. (April 2015) - Khalifeh, H.; Johnson, S.; Howard, L. M.; Borschmann, R.; Osborn, D.; Dean, K.; Hart, C.; Hogg, J.; Moran, P.
Abstract : Background: Little is known about the relative extent of crime against people with severe mental illness (SMI). Aims: To assess the prevalence and impact of crime among people with SMI compared with the general population. Method: A total of 361 psychiatric patients were interviewed using the national crime survey questionnaire, and findings compared with those from 3138 general population controls participating in the contemporaneous national crime survey. Results: Past-year crime was experienced by 40% of patients v. 14% of controls (adjusted odds ratio (OR) = 2.8, 95% CI 2.0–3.8); and violent assaults by 19% of patients v. 3% of controls (adjusted OR = 5.3, 95% CI 3.1–8.8). Women with SMI had four-, ten- and four-fold increases in the odds of experiencing domestic, community and sexual violence, respectively. Victims with SMI were more likely to report psychosocial morbidity following violence than victims from the general population. Conclusions: People with SMI are at greatly increased risk of crime and associated morbidity. Violence prevention policies should be particularly focused on people with SMI.